The tiger beetles (Coleoptera: Carabidae, Cicindelinae) of Angola: a descriptive catalogue and designation of neotypes - Serrano, Artur R.m.; Capela, Rúben A. (Zootaxa, 2013)
An annotated catalogue of the species and subspecies of tiger beetles (Coleoptera: Carabidae, Cicindelinae) hitherto known from Angola is given. A total of 89 forms (74 species and 15 subspecies) is recorded from this southwestern country of Africa. Within this assemblage there are 31 endemic forms (33.3%). Some species are represented by only the holotype specimen (some without locality) or the type series. Others were recorded based on a single specimen. Records for six species previously unknow from Angola are given: Foveodromica sp. n. 1, Foveodromica sp. n. 2, Ophryodera rufomarginata bradshawi Péringuey, 1888, Elliptica muata parallelestriata (W. Horn, 1923), Lophyra differens (W. Horn, 1892) and Myriochila jucunda (Péringuey, 1892). A historical review, as well as some considerations on the distribution and conservation status of these beetles in Angola are also presented.